Performance Evaluation of a Plug-in Hybrid Powertrain on Compression Ignition Engine in Terms of Energy Consumption Using Intelligent Cruise Control - Lewicki, Wojciech; Osipowicz, Tomasz; Abramek, Karol Franciszek; Mojsiuk, Hanna (Periodica polytechnica. Transportation engineering, 2025)
One of the contemporary trends is to emphasize the benefits of using hybrid drives over conventional ones. Due to the growing popularity of this category of drives, research on the optimization of energy consumption is becoming increasingly popular. The paper presents research on a selected plug-in hybrid drive unit of one of the most popular vehicle manufacturers in the European Union. The research process itself was based on the assessment of the use of active DISTRONIC cruise control as a tool that can influence the optimization of energy consumption of the tested drive unit. The experiment was conducted in real road conditions. Analyses were carried out for several drive system configuration modes: hybrid, E-mode, E-save and charging. The results of the experiment indicated the most optimal drive setting mode on expressways. These analyses emphasize the significant role of intelligent systems as a tool that allows for the optimization of energy consumption of vehicles equipped with plug-in hybrid units. The presented research is dedicated to users of this category of vehicles, while at the same time providing an answer to the question of how to effectively use the described drive unit in real operating conditions.